The Burdens-Benefits Ratio Consideration for Medical Administration of Nutrition and Hydration to Persons in the Persistent Vegetative State - Harvey, John C. (Christian bioethics, 2006)
In this article, Harvey notes the initial confusion about the statement made by the pope concerning artificial nutrition and hydration on patients suffering persistent vegetative states (PVS) due to misunderstanding through the translation of the pope's words. He clarifies and assesses what was meant by the statement. He also discusses the problems of terminology concerned with the subject of PVS. Harvey concludes that the papal allocution was in line with traditional Catholic bioethics, and that while maintaining the life of a patient is favorable, in particular cases this presumption wanes when it is clear that this treatment modality would be futile or very burdensome.